المراجعة التحليلية وآثارها على عملية المراجعة العامة للحسابات - زيود, لطيف; الأمين, ماهر; محمد, نـذيـر محمد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
المراجعة التحليلية هي تقنيات المراجعة المفيدة والمرتفعة العائد التي تستعمل جزئياً في كل عملية مراجعة،إذ تساهم بما يلي: - تساعد في تركيز الجهود عند القيام بالمراجعة. - تزويد المراجع بأدلة إثبات قيّمة لعملية المراجعة. - تستطيع أن تحدد وأن تقلل من أي تدقيق إضافي. - توجيه المراجع نحو التوسع في إجراءات المراجعة تجاه بنود محددة. تعتبر المراجعة الاختبارية ضرورة تفرضها اعتبارات الوقت والتكلفة لذلك أصبح مراجع الحسابات مضطراً للاعتماد على العينات الإحصائية أثناء قيامه بعملية المراجعة، الأمر الذي أدى إلى استخدام المراجعة التحليلية كأداة هامة في تحديد مسار عملية المراجعة بناءً على مؤشرات أساسية يعتمدها المراجع قبل وضع برنامجه أو الشروع بالمراجعة الميدانية، كما تستخدم المراجعة التحليلية كإجراءات جوهرية فيما إذا كانت أكثر تأثيراً وفعاليةً من الاختبارات التفصيلية. يهدف هذا البحث إلى توضيح ماهية المراجعة التحليلية وتحديد آثارها المختلفة على عملية المراجعة العامة للحسابات في مراحلها المختلفة، وبيان العوامل التي تؤثر على إمكانية الاعتماد عليها. Analytical auditing is a useful and cost effective technique that is partly used in the general audit. It assists in a number of ways: -It helps in concentrating efforts while auditing. -It provides the auditor with valid evidence valuable for auditing. -It can limit and reduce additional scrutiny. -It leads the auditor to extend the auditing procedures to specific items. Experimental auditing is considered a necessity dictated by time and price considerations. Therefore, while auditing, the auditor is obliged to count on statistic samples. This requires use of analytical auditing as a tool important for directing the auditing process depending on basic signs. The auditor uses those signs to lay out his plan or start auditing. Besides, analytical auditing is used because it here seems a more effective procedure than detailed experiments. This study tries to explain the nature of analytical auditing, identify its various effects on different phases of general auditing, and point to the factors that might negatively affect analytical auditing.